Media Framing of the Palestinian-Israeli Conflict After Yahya Sinwar’s Death: a Comparative Study of BBC News Arabic and Al-Jazeera - Wachid Hakim, Zumrotul Imanda; Zaini, Hisyam (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This research analyzes the framing strategies of BBC News Arabic and Al Jazeera in reporting the Israeli–Palestinian conflict after the death of Hamas leader Yahya Sinwar. Using Pan and Kosicki’s framing model, a qualitative descriptive-comparative method was applied to examine two news reports across four dimensions: syntactic, script, thematic, and rhetorical. The findings show distinct patterns: BBC News Arabic frames the conflict as unresolved, emphasizing Israel’s unachieved objectives, while Al Jazeera challenges Netanyahu’s victory claim and stresses Palestinian resilience. Beyond textual framing, these differences reveal contrasting ideological orientations in the Palestinian-Israeli conflict post-2024 context. BBC reproduces a state-centric and diplomatic discourse aligned with Western narratives, legitimizing Israel’s continued operations, whereas Al Jazeera advances a counter-hegemonic stance that resonates with Global South audiences by foregrounding resistance and anti-colonial struggle. These findings demonstrate how media framing not only structures news text. الملخص تدرس هذه المقالة استراتيجيات التأطير التي اعتمدتها بي بي سي العربية والجزيرة في تغطية الصراع الفلسطيني–الإسرائيلي بعد وفاة يحيى السنوار. وباستخدام نموذج بان وكوسيكي، اعتمدت الدراسة المنهج الوصفي المقارن النوعي لتحليل خبرين عبر أربعة أبعاد: النحوي، النصي، الموضوعي، والبلاغي. أظهرت النتائج اختلافاً واضحاً: بي بي سي العربية صوّرت الصراع كعملية لم تكتمل بعد، مؤكدة أن أهداف إسرائيل لم تتحقق، بينما رفضت الجزيرة رواية نتنياهو عن النصر وأكدت على صمود المقاومة الفلسطينية. و تكشف هذه النتائج عن توجهات أيديولوجية متباينة ؛ إذ تعيد بي بي سي إنتاج خطاب دبلوماسي متمركز حول الدولة ومنسجم مع السرديات الغربية يضفي شرعية على العمليات العسكرية الإسرائيلية، في حين تقدم الجزيرة خطاباً مضاداً للهيمنة يبرز المقاومة والنضال ضد الاستعمار، مما يتجاوب مع جمهور الجنوب العالمي. وتؤكد هذه النتائج أن التأطير الإعلامي يتضمن على بناء النصوص الإخبارية و صراعات أيديولوجية أوسع في تشكيل التصورات العالمية حول الصراع. Abstrak Penelitian ini menganalisis strategi framing BBC News Arabic dan Al Jazeera dalam pemberitaan konflik Israel–Palestina pasca kematian Yahya Sinwar. Dengan menggunakan model framing Pan & Kosicki, penelitian kualitatif dengan menggunakan metode deskriptif-komparatif ini menelaah dua teks berita melalui empat dimensi: sintaksis, naskah, tematik, dan retoris. Hasil penelitian menunjukkan perbedaan yang jelas: BBC News Arabic membingkai konflik sebagai proses yang belum selesai dengan menyoroti tujuan Israel yang belum tercapai, sedangkan Al Jazeera menolak klaim kemenangan Netanyahu dan menekankan keteguhan perlawanan Palestina. Lebih jauh, perbedaan tersebut mencerminkan orientasi ideologis yang kontras dalam konteks pasca-2024. BBC mereproduksi wacana negara-sentris dan diplomatik yang selaras dengan narasi Barat serta melegitimasi operasi militer Israel, sementara Al Jazeera menghadirkan posisi tandingan (counter-hegemonic) yang menekankan resistensi dan perjuangan antikolonial yang dekat dengan audiens Global South. Temuan ini menunjukkan bahwa framing media tidak hanya membentuk struktur teks, tetapi juga mencerminkan kontestasi ideologis dalam membangun persepsi global terhadap konflik.